Paket Pelatihan Psikodrama untuk Mengatasi Kecemasan Komunikasi Interpersonal Siswa - Permatasari, Devi; Sari, Eva Kartika Wulan (Jurnal Prakarsa Paedagogia, 2024)
This study produced a psychodrama training guidebook through group guidance to overcome interpersonal communication anxiety in students of SMAN Kota Malang. The method used in the study is development which has ten stages that have been modified into seven stages, including information gathering, planning, initial product development, initial product trials, product revision, main field trials, and main product revisions based on the assessment of six experts (stage 4), including material assessment, obtained an average score of 3.6. Media assessment obtained an average score of 3.6, it can be concluded that this guidebook is appropriate for use. Language assessment obtained an average score of 3.9, it can be concluded that in terms of language use, this guidebook is quite appropriate for use. While the assessment of product user tests (stage 6) by five Counselors at five different schools, obtained an average score of 3.7, it can be concluded that this guidebook has been tested directly by Counselor teachers at school so this guidebook is quite appropriate for use by counselors as a guideline in overcoming interpersonal communication anxiety in high school students. This guide has been revised according to the advice given by the expert so that the psychodrama training guide through group guidance to overcome interpersonal communication anxiety in students is categorized as very useful, very appropriate, very easy, very interesting, and very feasible to use. Suggestions for further researchers are expected to be able to develop the resulting development media by using trials on students to determine the level of effectiveness.